Developing ESP Learners Vocabulary Learning by Contextualization of the FonF Practice Model in CALL Context - shiva soltani; Ahmad Mohseni (Universitas Ahmad Dahlan, 2021)
The FonF practice model (focus on form) as a technology-oriented pedagogical model was contextualized to examine its efficacy on the second language (L2) learners' intentional and incidental vocabulary learning in computer-assisted language learning (CALL)as an attempt to integrate the emerging educational technologies into L2 learning. To this end, a sample of 55 medical ESP learners participated in a mixed methods research study that administered the FonF practice model-based treatment as the educational intervention among the experimental group. The findings confirmed the efficacy of the FonF practice model in developing incidental and intentional vocabulary learning among the participants who used technology-based tools at form, meaning, and communication levels. Theoretically, the main implication is the need to address individual differences in general and nonlinearity and dynamicity of motivation in particular. Pedagogically, L2 teachers are suggested to benefit from reported CALL tools to boost incidental and intentional vocabulary learning for ESP purposes.